Preliminary investigation of wake vortex generated by spinning quadrotor propellers using overset mesh - Nathanael, Joshua C. (2021)
As unmanned aircraft or drones are becoming more commonplace in our ever-developing environment where a number of drones can be flying in the same given airspace, a drone is likely to experience wake vortex turbulence from another drone nearby. Therefore, there is a need to understand how the airflow is generated from one vehicle and to what extent this airflow might affect another vehicle. Results of such studies will be useful in the establishment of safe separation for drone operations. In the present work, flow simulations are carried out using overset mesh on ANSYS Fluent 19.2 for both single and multiple propellers, and the flights in hovering and forwarding motion are considered. The simulation results obtained are in general agreement with the simulation and experimental results that are available from other studies. This provides support to the idea that the method of flow simulation can be acceptably reliable in predicting the resulting airflow from a flying drone and the proposed method can be further applied to various cases of drone flights.